Analysis of Dose Distribution and Risk of Pneumonitis in Stereotactic Body Radiation Therapy for Centrally Located Lung Tumors: A Comparison of Robotic Radiosurgery, Helical Tomotherapy and Volumetric Modulated Arc Therapy. (February 2015) - Kannarunimit, Danita; Descovich, Martina; Garcia, Aaron; Chen, Josephine; Weinberg, Vivian; Mcguinness, Christopher; Pinnaduwage, Dilini; Murnane, John; Gottschalk, Alexander R.; Yom, Sue S.
Stereotactic body radiation therapy (SBRT) to central lung tumors is associated with normal -tissue toxicity. Highly conformal technologies may reduce the risk of complications. This study compares physical dose characteristics and anticipated risks of radiation pneumonitis (RP) among three SBRT modalities: robotic radiosurgery (RR), helical tomotherapy (HT) and volumetric modulated arc therapy (VMAT). Nine patients with central lung tumors ≤5 cm were compared. RR, HT and VMAT plans were developed per RTOG 0831. Dosimetric comparisons included target coverage, conformity index, heterogeneity index, gradient index, maximal dose at 2 cm from target (D2 cm), and dose-volume parameters for organs at risk (OARs). Efficiency endpoints included total beam-on time and monitor units. RP risk was derived from Lyman-Kutcher-Burman modeling on in-house software. The average GTV and PTV were 11.6 ± 7.86 cm 3 and 36.8 ± 18.1 cm 3 . All techniques resulted in similar target coverage (p = 0.64) and dose conformity (p = 0.88). While RR had sharper fall-off gradient (p = 0.002) and lower D2 cm (p = 0.02), HT and VMAT produced greater homogeneity ( p < 0.001) and delivery efficiency (p = 0.001). RP risk predicted from whole or contralateral lung volumes was less than 10%, but was 2-3 times higher using ipsilateral volumes. Using whole (p = 0.04, p = 0.02) or ipsilateral (p = 0.004, p = 0.0008) volumes, RR and VMAT had a lower risk of RP than HT. Using contralateral volumes, RR had the lowest RP risk (p = 0.0002, p = 0.0003 versus HT, VMAT). RR, HT and VMAT were able to provide clinically acceptable plans following the guidelines provided by RTOG 0813. All techniques provided similar coverage and conformity. RR seemed to produce a lower RP risk for a scenario of small PTV-OAR overlap and small PTV. VMAT and HT produced greater homogeneity, potentially desirable for a large PTV-OAR overlap. VMAT probably yields the lowest RP risk for a large PTV. Understanding subtle differences among these technologies may assist in situations where multiple choices of modality are available.